Molecular level dependencies of water permeability in di-block copolymer assemblies - Hasheminejad, Kourosh; Jaques, Ygor Morais; Lepo, Anneli; Scacchi, Alberto; Sammalkorpi, Maria (Elsevier BV, 2025)
Atomistic detail molecular dynamics (MD) simulations were used to examine molecular level dependencies of water interactions and permeability of amphiphilic di-block copolymer assemblies. Four different linear amphiphilic di-block copolymers, with chemically identical hydrophilic blocks but varying hydrophobic blocks, were studied. The simulations show that while all examined di-block copolymers formed assemblies highly efficient in blocking water, the ability of the assemblies to sustain their water blocking character when subject to lateral strain had significant differences. The assemblies retaining high internal order under lateral strain were most efficient in moisture blocking. In this, flexible side chains with branching filling the surroundings with hydrophobic groups to prevent molecular level water penetration, were important. Moreover, styrene rings provided efficient, space-filling moisture protection blocks, demonstrating further the importance of flexible spatial orientation hydrophobic side chains. The simulations also connect the roughness and interfacial fluctuations of the block-copolymer assembly with water penetration. The work shows molecular level design principles for enhancing moisture preventing coatings and gives insight into engineering the performance of other filtration systems.